Accommodation centres for asylum seekers as sites of conflict and collaboration: Strategies for the prevention of violence - Noa Milman; Sifka Etlar Frederiksen (Culture, Practice & Europeanization)
The political use of mass accommodation for governing asylum seekers is growing in frequency, despite its documented disadvantages for asylum seekers’ wellbeing and protection. So long as mass accommodation of asylum seekers is used by states, it is necessary to ask how violence is handled and prevented in these institutions. Using interview data from 80 residents and employees in two German accommodation centres, our findings illustrate the central role of low-level employees and residents in protection against violence. We analyse the interlinked strategies that both of these populations employ, highlighting residents’ agency and the previously overlooked cosmopolitan imaginations of low-level employees. We conclude the paper by contextualising our findings and recommending future actions.